ESTADO FINANCIERO COMO FACTOR DESENCADENANTE EN LA TOMA DE DECISIONES ESTRATEGICOS EN UNA COMPAÑÍA ELECTRICA EN LA REGION ICA, DURANTE EL PERIODO 2019 - HERNANDEZ CORDOVA, ROXANA GISSELA (2020)
The Electric Distribution Companies, as network industries, have the mission of transporting and distributing energy from specific points on the high or medium voltage lines, to deliver final consumers at voltage levels appropriate for industrial and domestic use. This activity is organized in public service companies, which obtain energy supplies through contracts with generators. These companies, like any other in the course of their operational and strategic processes, permanently make decisions, however, some of them do not use the tools available to them due to the minimal importance they assign or simply because the data they contain does not reflect the situation. nor results of the company. The Financial Statements are fundamental in the decision-making process and provide periodic reports on specific dates, on the state or development of the administration of a company, that is, the information necessary for decision-making in a company. Decision making according to Tanaka Nakasone, Rodriguez Ponce & Pedraja Rejas (2008) constitutes an election process that involves the allocation of the necessary resources to achieve or maintain a competitive advantage. From this perspective, it can be deduced that a very objective measure of decision-making is a competitive advantage that can be analyzed through 2 relevant items; efficiency and market position.